Genetic architecture of post-harvest tuber quality traits in bush yam (Dioscorea praehensilis Benth.) germplasm through association mapping - Adewumi, A.S.; Asare, P.A.; Akintayo, O.T.; Adejumobi, I.I.; Adu, M.O.; Taah, K.J.; Afutu, E.; Opoku, V.A.; Stanley, A.; Akaba, S.; Mondo, J.; Mushoriwa, H.; et al. (Frontiers Media, 2024)
Introduction: Bush yam (Dioscorea praehensilis Benth.) is an important semi-domesticated food crop in West Africa. Limited information on the genetic architecture and its poor post-harvest tuber quality traits significantly hinder its use as food and source of income. Hence, dissecting the genetics underlying the expression of its post-harvest tuber quality traits is essential for establishing proper breeding schemes.